2011
DOI: 10.1097/ta.0b013e31820ebee1
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Related to Dysautonomia After Severe Traumatic Brain Injury

Abstract: Dysautonomia frequently occurs in patients with severe TBI. A younger age and DAI could be risk factors for facilitating the development of dysautonomia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 21 publications
1
34
1
6
Order By: Relevance
“…69 Young age and diffuse axonal injury are risk factors for developing PSH. 70 There are no specific guidelines for managing PSH. The evidence for drug therapy is limited to case reports or case series, and includes opiates, GABA agonists, α- and β-blockers, and dopamine agonists with varying effectiveness.…”
Section: Management Of Complications and Other Neurocritical Care Issuesmentioning
confidence: 99%
“…69 Young age and diffuse axonal injury are risk factors for developing PSH. 70 There are no specific guidelines for managing PSH. The evidence for drug therapy is limited to case reports or case series, and includes opiates, GABA agonists, α- and β-blockers, and dopamine agonists with varying effectiveness.…”
Section: Management Of Complications and Other Neurocritical Care Issuesmentioning
confidence: 99%
“…While research directly examining autonomic regulatory changes following concussion is limited, some support comes from the literature on severe traumatic brain injury (TBI). Significant changes in cardiac autonomic control after TBI have been reported, including parasympathetic withdrawal from the cardiac rhythm (resulting in severe cardiac abnormalities), orthostatic intolerance, and tachycardia [11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…PSH occurs in about 10% of sTBI patients[8082], and is associated with younger age, more severe injury, early fever [83] and diffuse axonal injury [82, 84]. While recovery from the complication is possible, those with PSH generally have longer hospital and ICU stays, greater costs, and possibly worse outcomes [80, 85].…”
Section: Specific Strategies For Medical Managementmentioning
confidence: 99%
“…Several small, early-stage clinical trials [8485] also suggested that acute progesterone administration may improve neurologic outcomes patients with sTBI [98]. Based on these findings, the efficacy of progesterone was recently studied in two Phase III trials.…”
Section: Pharmacologic Neuroprotective Strategiesmentioning
confidence: 99%